Factors associated with the responsive behaviours of older adults living in long-term care homes towards staff: a systematic review protocol. Issue 5 (28th May 2019) - Song, Yuting; Hoben, Matthias; Weeks, Lori; Boström, Anne-Marie; Goodarzi, Zahra S; Squires, Janet; Doan, Helen; Wagg, Adrian; Reid, R Colin; Estabrooks, Carole
Abstract : Introduction: In the last decade, increasing research interest has been expressed in responsive behaviours of older adults living in long-term care (LTC) homes, including nursing homes and assisted living facilities. Responsive behaviours are not only a sign of underlying unmet needs, but when directed against (towards) paid staff can lead to decreased quality of work life, and may contribute to lower quality of care. In this systematic review, we aim to synthesise empirically based quantitative and qualitative evidence on factors and stakeholder (eg, staff and family members) experiences of factors associated with the responsive behaviours of people living in LTC directed towards staff. Methods and analysis: This study will be a systematic review of published and 'grey' literature. Twelve bibliographical databases will be searched, and for each database, we will use appropriate subject headings and keywords that cover two concepts: LTC and responsive behaviour. No publication date or language filter will be used. The title and abstract of each extracted record will be screened, followed by screening of full text of included papers. Then data extraction and quality assessments will be undertaken. Each stage will be completed independently by pairs of authors. For quantitative studies, meta-analysis will be conducted if pooling is possible; otherwise, a critical narrative analysis will be conducted. For qualitative studies, thematic analysis will be conducted. Factors will then be organised at the individual, interpersonal, institutional and larger societal levels. Sensitivity analysis will be conducted to explore the influence of risk of bias and publication bias on the results. Subgroup analysis will be conducted for people who live with dementia and those who do not. Ethics and dissemination: Ethics approval is not required for this systematic review. The results of this study will be disseminated via peer-reviewed publication and presentation at professional conferences.